Critical Attitude to the Organization and Methods of Teaching and Learning in Jaded Schools and Madrassas in the Doctrines of Abdurauf Fitrat - Pirjonovich Qabulov, Qosimboy; Zokirjonovna Rakhimova Mo'minа (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the organization of training and education in schools and madrassas of Jadid according to the views of Abdurauf Fitrat and their critical attitude to the teaching method. It scientifically substantiates the conclusion that the only correct way to save the nation from enslavement is to improve first the upbringing and education and then the development of society through reforms. In particular, Abdurauf Fitrat bases teaching methods in primitive, higher, secondary, and new schools on his works “Teaching” from the textbook, “Questions of Spelling,” “On the Rules of the Uzbek Language,” and “Rules of Literature.”